Direct visualization of vibration modes of microobjects using an LCoS SLM in a Twyman-Green interferometer - Kacperski, Jacek; Kujawinska, Malgorzata (Photonics Letters of Poland, 2010)
The modification of a classical Twyman-Green interferometer by implementation of Liquid Crystal on a Silicon (LCoS) Spatial Light Modulator (SLM) as a reference mirror allows introducing an arbitrary phase in the reference wavefront. This special capability is applied to facilitate the measurements of mechanically active microelements (MEMS). Thanks to compensation of the initial shape of an element under test, it is possible to directly visualize vibration mode shapes even for non-flat objects and determine resonance frequencies of microelements. The description of the measurement system, methodology of the visualization and selected results obtained for a silicon micromembrane are presented. Full Text: PDF References: H. J. Tiziani, J. Liesener, C. Pruss, S. Reichelt, L. Seifert, “Active wavefront shaping and analysis”, Proc. SPIE, 776, 1-9, (2005).[CrossRef] J. Kacperski, M. Kujawińska, “Active, LCoS based laser interferometer for microelements studies”, Optics Express 14 (21), 9664-9678, (2006). [CrossRef] S. Petitgrand, R. Yahiaoui, A. Bosseboeuf, K. Danaie, “Quantitative time-averaged microscopic interferometry for micromechanical device vibration mode characterization”, Proc. SPIE 4400, 51-60, (2001). [CrossRef] K. Patorski, Z. Sienicki, M. Pawłowski, A. Styk, A. Jóźwicka, “Studies of the properties of the temporal phase shifting method applied to silicone microelement vibration investigations using the time average method”, Proc. SPIE 5458, 208-219, (2004). [CrossRef] K.G. Larkin, “Efficient nonlinear algorithm for envelope detection in white light interferometry”, J. Opt. Soc. Am. A 13, 832-843, (1996). [CrossRef]